Examination of parental dieting and comments as risk factors for increased drive for thinness in men and women at 20‐year follow‐up. Issue 5 (16th August 2016) - Klein, Kelly M.; Brown, Tiffany A.; Kennedy, Grace A.; Keel, Pamela K.
ABSTRACT: Objective: Popular beliefs suggest that parents influence children's eating disorder risk through modeling pathological behaviors and attitudes, and this history may contribute to disordered eating in adulthood. However, the empirical basis for this popular thinking is limited by a reliance on cross‐sectional designs that do not distinguish between maternal and paternal influences and use primarily child and adolescent samples. To address these limitations, the present study examined the impact of maternal and paternal dieting and comments about weight and eating, as reported by late adolescents, on the eating pathology of those late adolescents at 20‐year follow‐up. Method: Data were drawn from a longitudinal epidemiological study of health and eating patterns in a cohort of randomly sampled college students established in 1992 ( N  = 799; mean age: 19.87 [±1.64] years; 70.8% women) and followed 20 years later in 2012 ( N  = 539). Results: At baseline, there were no gender differences in reported rates of maternal or paternal dieting. Both men and women reported higher levels of maternal versus paternal dieting. Further, women endorsed higher levels of maternal and paternal comments on their own weight and eating. A multivariable model in women supported that maternal dieting and paternal comments significantly predicted drive for thinness at follow‐up. No parental variables predicted drive for thinness in men at follow‐up. Discussion: While our study supports parental influence on children's eating attitudes, it suggests a need to consider gender and mode of influence. Prevention efforts focused on challenging cultural standards of appearance may benefit from incorporation of parents. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:490–497)